Pathogenicity of Beauveria bassiana Vuill in compost media for Oryctes rhinoceros L. oil palm pest control - Rina Novianti; Hafiz Fauzana; Rusli Rustam (CROPSAVER, 2021)
The Oryctes rhinoceros pest is an important pest of palm oil plant.  Pest problems occur because  Oil Palm Empty Fruit Bunches (OPEFB) is added for soil fertility to create a breeding site for larvae O. rhinoceros. Generally, OPEFB will receive the plants more quickly when composted, and pest control is carried out in the compost. Biological control is more recommended because it is environmentally friendly, Therefore compost is added with biological control agent O. rhinoceros namely B. bassiana. This study is aimed to obtain the best conidia density of Beauveria bassiana in compost in controlling larvae O. rhinoceros. The research was carried out at the Plant Pest Laboratory and Experimental Garden, Faculty of Agriculture, Riau of University. The study was carried out from February to November 2020. The experiment on the conidia density of B. bassiana fungi in compost media against larvae O. rhinoceros, using a Completely Randomized Design (CRD), with 6 treatments 4 replications obtained 24 experimental units, while the treatments were 0 g.l-1, 15 g.l-1, 30 g.l-1, 45 g.l-1, 60 g.l-1 and 75 g.l-1. The results of the research revealed that  OPEFB compost + sawdust containing the fungus B. bassiana 75 g.l-1 (83,2 x108 kon/ml) had the best ability to control larvae O. rhinoceros with a total larvae mortality of 87% which caused early death of 54 hours after application, LT50 of 213 hours after application, and LC50 of 3,3% or the equivalent of 33 g.l-1 at 14 days after application.